The changing landscape of school choice in Canada: From pluralism to parental preference? - Bosetti, Lynn; Van Pelt, Deani; Allison, Derek (Education Policy Analysis Archives, 2017)
This paper provides a descriptive account of the growing landscape of school choice in Canada through a comparative analysis of funding and student enrolment in the public, independent and home-based education sectors in each province. Given that the provinces have responsibility for K-12 education, the mixture of public, independent and home school education varies rather widely by province, as does the level of funding and regulation. Delivery and funding of public education in Canada has long prioritized limited linguistic and religious pluralism, providing various options for English or French, and Catholic or Protestant alternatives to qualified parents. More recently growing numbers of parents have been seeking more options for their children’s education. This has fueled slow but steady growth in independent schools and home schooling.